2013
DOI: 10.1093/carcin/bgt140
|View full text |Cite
|
Sign up to set email alerts
|

Grape antioxidant dietary fiber inhibits intestinal polyposis in Apc Min/+ mice: relation to cell cycle and immune response

Abstract: Epidemiological and experimental studies suggest that fiber and phenolic compounds might have a protective effect on the development of colon cancer in humans. Accordingly, we assessed the chemopreventive efficacy and associated mechanisms of action of a lyophilized red grape pomace containing proanthocyanidin (PA)-rich dietary fiber [grape antioxidant dietary fiber (GADF)] on spontaneous intestinal tumorigenesis in the Apc(Min/+) mouse model. Mice were fed a standard diet (control group) or a 1% (w/w) GADF-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 37 publications
0
18
0
2
Order By: Relevance
“…(5) A reduction of intestinal tumorigenesis in APC Min/þ mice, an animal model of colorectal cancer, including significant reductions in the number (276 %) and size (265 to 2 87 %) of polyps (88) . (6) Modifications in gene expression in healthy mice and in APC Min/þ mice, in particular, down-regulation of genes associated with tumour development and proto-oncogenes (for example, genes belonging to the RAS family, such as RASSF4, RAP2C and RAP2B), and up-regulation of tumour-suppressor genes (for instance, NLB1 or TGFb3, related to cell cycle and cell proliferation, respectively) (87,88) .…”
Section: Gastrointestinal Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) A reduction of intestinal tumorigenesis in APC Min/þ mice, an animal model of colorectal cancer, including significant reductions in the number (276 %) and size (265 to 2 87 %) of polyps (88) . (6) Modifications in gene expression in healthy mice and in APC Min/þ mice, in particular, down-regulation of genes associated with tumour development and proto-oncogenes (for example, genes belonging to the RAS family, such as RASSF4, RAP2C and RAP2B), and up-regulation of tumour-suppressor genes (for instance, NLB1 or TGFb3, related to cell cycle and cell proliferation, respectively) (87,88) .…”
Section: Gastrointestinal Healthmentioning
confidence: 99%
“…Wistar rats, n 10 Reduction of lipid oxidation in distal colonic mucosa (2 25 %) (86) Grape antioxidant dietary fibre 0·1 g/kg bw, 2 weeks C57BL/6J mice, n 8 Overexpression of enzymes pertaining to the xenobiotic detoxifying system and endogenous antioxidant cell defences (þ100 to þ 200 %) (87) Grape antioxidant dietary fibre 0·1 g/kg bw, 2 weeks C57BL/6J mice, n 8 Down-regulation in colon mucosa of genes associated with tumour development and proto-oncogenes (2 100 to 2 200 %), up-regulation of tumour-suppressor genes (þ 100 %) (87) Grape antioxidant dietary fibre 1 % of the diet, 16 weeks APC Minþ/2 mice, n 12 Reduction in the number (2 76 %) and size (2 65 to 2 87 %) of polyps (88) Grape antioxidant dietary fibre 5 -7 % of the diet, 4 weeks…”
Section: Cvd Risk Factorsmentioning
confidence: 99%
“…A grape anti‐oxidant dietary fiber treatment, consisting of soluble phenolics, insoluble phenolic acids, and other components of the dietary fiber fraction, including polysaccharides and lignins, prevented polyp formation by ∼81% in Apc Min/+ mice by modifying cell cycle genes. DNA microarray analysis of colonic mucosa revealed downregulation of immune response genes (CXCR4 signaling via second messenger, T‐cell receptor, and CD28 costimulation in activation of nuclear factor‐κB, inducible T‐cell co‐stimulator pathway in T‐helper cells, T‐cell receptor signaling pathway, nuclear factor of activated T cells in immune response) in the colonic mucosa of treated animals compared with untreated animals . Several dietary fiber studies conducted by our group suggest that a high‐fiber diet protects against colon and other cancers; the lipid fraction of wheat bran fiber in particular provides maximal protection against AOM‐induced colon cancer in rats .…”
Section: Polyunsaturated Fatty Acids Eicosapentaenoic Acid (Epa; 20:mentioning
confidence: 94%
“…One group treated Apc Min/ + mice either a control diet (Teklad Global 18% Protein rodent diet), or the control diet supplemented with 1% grape antioxidant dietary fiber (GADF), a lyophilized red grape pomace containing proanthocyanidins-rich dietary fiber, for 6 weeks [48]. This study found that GADF suppressed the intestinal tumor development, and downregulated several genes associated with the immune response, such as CXCR4 signaling, which has been reported to be involved in the tumorigenesis and lymph node metastasis.…”
Section: Studies Of Tumor-bearing Animal Modelsmentioning
confidence: 99%